Magnesium sulfate has sex-specific, dose-dependent vasodilator effects on preterm placental vessels. Issue 1 (December 2015) - Gray, Clint; Vickers, Mark; Dyson, Rebecca; Reynolds, Clare; Berry, Mary
Abstract Background Women at risk of preterm delivery receive magnesium sulfate (MgSO4 ) in the pre-delivery phase to reduce their child's risk of neurodevelopmental complications associated with preterm birth. However, the mechanisms underpinning its placental vascular role remain uncertain. Methods The aim of this study was to examine MgSO4 action on vascular tone in male and female human placental vessels from term and preterm deliveries. Vessels were obtained from placental biopsy following birth at term (37–41 weeks) or preterm gestation (<36 weeks of gestation). The vessels were mounted on a pressure myograph, pre-constricted with synthetic endoperoxide prostaglandin PGH2 (U46619) (0.1–100 μmol/l), and percentage of relaxation was calculated following incubation with bradykinin. Experiments were carried out in the presence of MgSO4 (0.2 mmol/l), NΨ -nitro-L-arginine methyl ester (L-NAME) (0.1 mmol/l), indomethacin (10 μmol/l), Ca2+ -activated K+ channel blocker TRAM-34 (1 μM) and apamin (3 μM) to assess mechanisms of vascular function. Vascular [calcium ions (Ca2+ )] was analysed using a colorimetric calcium assay. Results Vasodilation in vessels from preterm males was significantly blunted in the presence of MgSO4 when compared to preterm female and term male and female vessels. Overall, MgSO4 was observed to differentially modulate placental vascular tone and vascular calcium concentrations in a sex-specific manner. Conclusions As MgSO4 regulates human placental blood flow via specific pathways, foetal sex-specific MgSO4 treatment regimes may be necessary. In an era of increasing awareness of individualised medicine, sex-specific effects may be of importance when developing strategies to optimise care in high-risk patients.